KARAKTERISTIK DAN MUTU BERAS LOKAL KABUPATEN BULUNGAN KALIMANTAN UTARA: (Characteristics And Quality Of Local Rice In Bulungan District, North Kalimantan) - Fitrah Pangerang; Nila Rusyanti (jurnal1, 2018)
The quality of rice determines rice prices and consumer tastes. This study aims to identify the characteristics and quality of local rice based on SNI 01-6128-2015 standards. This research was conducted by exploration method. The amount of rice taken is 1 kg. Each local rice is observed for its physical properties and quality. Physical properties include white degree, clarity, shape and size of rice while the quality of rice is adjusted to the standard quality SNI 01-6128-2015. The results show that the physical properties of local rice have white degrees which vary between 58.8 - 54.6%. Where the type of krayan rice and rice taro shows the highest white degree. The value of clarity of local rice shows in the range of 1.70 - 2.57%. The level of rice clarity affects the level of consumer preference. The size of local rice has a long and medium sized category. Long-term rice is Puy, Ikang, Angga and Red rice which are cultivated with traditional lowland rice farming systems with a length (6.5-7) mm. While medium-sized rice is the type of krayan rice and taro rice which are cultivated organically with traditional rice farming systems by the people of the highlands with a length (5.5-5.6) mm. The form of local rice has the form of lean rice (2.8-3.5) and the form of medium rice (2.2-2.8). Ikang rice, Angga and krayan have a slim shape while Puih, Keladi and Merah have medium forms. Judging from the rice quality requirements of the SNI standard (2015), it can be seen that the local rice in Bulungan meets the requirements for quality standards for rice III, IV and V. Ikang and Krayan rice meets III quality. Puy, Angga and Keladi rice meets the quality of rice IV. While brown rice fulfills the quality of rice V. This shows that the local rice in Bulungan definitely needs better postharvest handling to improve the quality of rice so that the rice produced is able to compete in the market. Conclusion Bulungan local rice has characteristics with the size and shape of lean and medium rice with a relatively low quality